PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN CUSTOMER EXPERIENCE TERHADAP WORD OF MOUTH PADA SKINCARE BRAND EMINA - Maknun, Luklu'ul; Mahendri, Wisnu (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research aims to find out: 1) product quality influences word of mouth, 2) price perception influences word of mouth, 3) customer experience influences word of mouth, product quality, price perception and customer experience simultaneously influence word of mouth. mouth on Emina's bran skincare. The population in this research are consumers who use Emina products. The sampling technique used purpose sampling, data was obtained by distributing questionnaires to 90 respondents. The data analysis technique in this research is descriptive analysis, classical assumption testing and Multiple Linear Regression analysis using the SPSS Statistics 26 application. The results of the research show that: 1) product quality influences word of mouth, 2) price perception influences word of mouth, 3) customer experience influences word of mouth, product quality, price perception and customer experience simultaneously influence word of mouth. Keywords: product quality, price perception, customer experience and word of mouth